APGAR Score in Pregnant Women Infected with Covid-19 - Siti Choirul Dwi Astuti; Rabia Zakaria (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2022)
The number of confirmed cases of Covid-19 is increasing. In Indonesia, 52% of pregnant women are infected with Covid19. Women who are confirmed positive will experience long-term effects, especially pregnant women. This study aimed to determine APGAR skor yang dilahirkan oleh ibu hamil yang pernah terinfeksi Covid-19. The population in this study was 33 pregnant women who had been infected with Covid-19 during pregnancy, and all of them were sampled in this study because the sampling used a total sampling technique. The method used is an observational cohort study. The measuring instrument in this study used an observation sheet. Data analysis using the ANOVA test. The results of this study, a p-value of 0.142, are more significant than 0.05, indicating the hypothesis is rejected. There is no significant difference in APGAR scores in pregnant women who have been infected with Covid-19 in the 1st trimester, 2nd trimester or 3rd trimester. This happens because there is a possibility that Covid-19 in the study sample is not the only risk factor that affects the APGAR score.